2015
DOI: 10.1007/s12664-015-0546-7
|View full text |Cite
|
Sign up to set email alerts
|

An innovative modification of sandwich embolization technique for simultaneous management of ruptured pseudoaneurysm of branch of splenic artery and hypersplenism syndrome

Abstract: Pancreatitis induced ruptured pseudoaneurysm (PSA) of the peri-pancreatic and splenic arteries may become a source of life-threatening hemorrhage. Its management is challenging and requires an individualized and multidisciplinary approach. The index case is a 32-year-old chronic alcoholic male presented with multiple episodes of hematemesis and melena. Pathological and imaging findings were consistent with anemia and acute pancreatitis with ruptured PSA of branch of splenic artery, portal cavernoma formation, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
3
0
2

Year Published

2018
2018
2018
2018

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 6 publications
0
3
0
2
Order By: Relevance
“…1,11 If it is not treated promptly, the risk of rupture is in the range of 37-47% 12,13 and the mortality rate is 90%. 5,12,13 In the case described here, the patient was admitted because of symptoms related to PASA rupture: upper digestive hemorrhage with hemodynamic instability.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…1,11 If it is not treated promptly, the risk of rupture is in the range of 37-47% 12,13 and the mortality rate is 90%. 5,12,13 In the case described here, the patient was admitted because of symptoms related to PASA rupture: upper digestive hemorrhage with hemodynamic instability.…”
Section: Discussionmentioning
confidence: 99%
“…[13][14][15][16] The most common causes of PASA include local inflammatory states (primarily chronic and acute pancreatitis) and trauma. 4,5,[11][12][13]17 Tessier et al 4 reported associations with pseudocysts in 41% of cases of pancreatic PASA. Among other less frequent causes, Hartman et al 17 described a PASA associated with scleroderma and gastric ulcer, with no history of pancreatitis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Apesar de o PSAE ser o aneurisma visceral mais comum, ainda assim é uma entidade rara (STICCO, et al, 20016;SCHATZ, et al, 2015). Caso não seja tratado precocemente, apresenta risco de ruptura de 37-47% e taxa de mortalidade de 90% (MANOJ et al, 2015;SAWICKI et al, 2015;FERREIRA et al, 2013). Neste caso, a paciente foi internada pelos sintomas relativos à ruptura do PSAE: hemorragia digestiva alta, cursando com instabilidade hemodinâmica.…”
Section: Discussionunclassified
“…A má digestão, a má absorção de nutrientes, a restrição alimentar em função das dores abdominais e o consumo de álcool são fatores que contribuem para a desnutrição proteico-calórica instalada nesses pacientes. É frequente a presença da subalimentação, associados à diarreia e esteatorreia comprometendo ainda mais no estado nutricional (MANOJ et al, 2015).…”
Section: Introductionunclassified